Do information and communication technologies empower female workers? Firm-level evidence from Viet Nam - Natalie Chun; Heiwai Tang (Asian Development Bank (ADB), 2018)
This paper studies the effects of firms' investments in information and communication technologies (ICT) on their demand for female and skilled workers. Using the gradual liberalization of the broadband Internet sector across provinces from 2006 to 2009 as a source of exogenous variation to identify the causal impacts of ICT, we find evidence from the country's comprehensive enterprise survey data that firms' adoption of broadband Internet and other related ICT increased their relative demand for female and college-educated workers. The effect of ICT on firms' female employment is particularly strong among the college-educated workers, and is stronger in industries that are more dependent on highly manual and physical tasks. These results suggest that ICT can lower gender inequality in the labor market by shifting the labor demand from highly manual, routine tasks in which men have a comparative advantage toward more nonroutine, interactive tasks in which women hold a comparative advantage. However, the effect of ICT is weaker in industries relying more on complex and interactive tasks, suggesting that gender differences in education may have limited female labor supply for the most innovative industries that require highly technical skills to complement ICT.
Keywords: I24; J16; J21; J22; 330; gender inequality; ICT; information technology; infrastructure; wage inequality